DESCRIPTION OF STRESS LEVEL OF FINAL LEVEL STUDENTS OF SUTOPO'S D3 NURSING PROGRAM IN PREPARING SCIENTIFIC WRITINGS - Rahmawati, Anggie (Global Ten Public Health and Nursing Journal, 2024)
Stress is an unpleasant psychological process that occurs in response to the environment. Stress occurs when there is an event which will then become something that is felt to be dangerous for the individual, from there the individual will react, both physically and psychologically. The purpose of this research is to find out how the description of the level of stress in Sutopo's final year D3 Nursing students is in compiling work scientific writing. This type of research is descriptive research using a questionnaire method using a Depression Anxiety Stress measuring instrument questionnaire (DASS 42) filled out by final year students of Sutopo's D3 Nursing Study Program. Determination of the sample in this study using random sampling, obtained 48 students. The results of this study showed that most of the characteristics of students based on age (75%) were 21 years old, almost all of the characteristics of students based on gender (89.6%) were female. Almost half of the stress levels experienced by level 3 students were moderate stress (35.4%), almost half experienced mild stress (33.3%), a small portion was severe stress (14.6%), and a small proportion were not stressed (16.7 % ). From the results of this research, it can be concluded that almost half of the final year students of Sutopo's D3 Nursing Study Program experience moderate stress in compiling scientific papers.